2017
DOI: 10.2527/jas2017.1870
|View full text |Cite
|
Sign up to set email alerts
|

Effect of floor space allowances on growth performance of finishing pigs marketed at 138 kilograms1,2,3

Abstract: Current floor space allowances were determined in research studies conducted 10 to 20 yr ago using pigs that were marketed at a BW of about 113 kg or less. Currently, pork producers are regularly marketing pigs that weigh over 128 kg. Given this precipitous increase in market weight, we conducted 2 experiments to determine if floor space allowances previously determined apply to pigs marketed at greater than 128 kg. Experiment 1 was conducted at 5 university research stations throughout the Upper Midwest regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
0
15
1
Order By: Relevance
“…More recently, 2 studies (Flohr et al, 2016;Thomas et al, 2017) have applied these equations in both commercial and research environments and found reductions in performance due to inadequate space allowance at lighter BWs than predicted previously. Johnston et al (2017) also observed that floor space allowance predicted by Gonyou et al (2006) might be underestimated for heavy weight market pigs. In the study herein, we used a limited number of pigs per pen (7 or 8) relative to what is frequent observed in commercial production (25 to 30 pigs per pen).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…More recently, 2 studies (Flohr et al, 2016;Thomas et al, 2017) have applied these equations in both commercial and research environments and found reductions in performance due to inadequate space allowance at lighter BWs than predicted previously. Johnston et al (2017) also observed that floor space allowance predicted by Gonyou et al (2006) might be underestimated for heavy weight market pigs. In the study herein, we used a limited number of pigs per pen (7 or 8) relative to what is frequent observed in commercial production (25 to 30 pigs per pen).…”
Section: Discussionmentioning
confidence: 91%
“…Gonyou et al (2006) proposed a critical k value, 0.0336, and suggested that pig growth should not be decreased until their BW reaches the critical point where there is inadequate space to maintain maximal growth rate. However, recent studies (Flohr et al, 2016;Johnston et al, 2017;Thomas et al, 2017) demonstrated that growth reductions due to inadequate space may start to occur at k value above 0.0336.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research evaluating space allowance (either by changing pen inventory or adjustable gating) for pigs raised to modern market weights continues to report decreased growth rate as a consequence of reduced FI ( Johnston et al, 2017 ; Thomas et al, 2017 ; Carpenter et al, 2018 ). Thomas et al (2017) and Carpenter et al (2018) reduced floor space in pens with fixed inventories and observed decreased ADG and ADFI, with these reductions occurring from ~70 kg BW, or prior to reaching the critical k -value.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike growth rate and FI, the effects of space allowance on gain efficiency in the literature are more variable. Several have reported no evidence for differences ( Johnston et al, 2017 ; Thomas et al, 2017 ; Carpenter et al, 2018 ), while others observed decreased G:F as floor space becomes restricted ( NCR-89 Committee on Confinement Management of Swine, 1993 ; M. C. Brumm and NCR-89 Committee on Management of Swine, 1996; Street and Gonyou, 2008 ). Possible mechanisms for decreased G:F accompanying floor space restriction include decreased protein deposition ( Chapple, 1993 ), increased activity, and increased trips to the feeder in crowded pens ( Shull, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation